Modernizing Student Enrollment Processes through Web-Based Systems: A Case Implementation at MA Al-Aqsha Massaile - Utami, Listia; Markani, Markani; Awaliyah, Neneng; Asnimar, Asnimar; Sabitu, Kamoru; Saifullah, Saifullah (Ceddi Journal of Education, 2025)
The rapid advancement of information technology has significantly influenced the transformation of administrative processes in the education sector. At MA Al-Aqsha Massaile, the student admission process had previously been conducted manually, leading to data management inefficiencies, extended queues, and delays in selection result announcements. This study aims to design and implement a web-based student admission information system to enhance efficiency, accuracy, and user satisfaction. The research adopted a qualitative and system development approach, involving interviews with school administrators to identify workflow challenges, followed by system development using the waterfall model. System testing and evaluation were conducted through user trials involving 30 respondents, including prospective students, parents, and school staff. The results indicate that 93.3% of users rated the system as "very effective" in simplifying the registration process, while 90% found the user interface intuitive and easy to navigate. Furthermore, 86.7% of respondents agreed that the system reduced errors in data input and improved the overall registration experience. These findings confirm that the web-based system significantly improves administrative efficiency and user experience in student admissions. Future recommendations include integrating the system with academic databases and implementing mobile-friendly features to support wider accessibility.